Association of Central Obesity With All Cause and Cause-Specific Mortality in US Adults: A Prospective Cohort Study - Huai, Pengcheng; Liu, Jian; Ye, Xing; Li, Wen-Qing (Frontiers in Cardiovascular Medicine, 2022)
Background：Previous data on the association between central obesity and mortality are controversial. The aim of this study was to determine the associations between central obesity, as measured by the waist-to-height ratio (WtHR) and waist circumference (WC), with all cause and cause-specific mortality in U.S. adults. Methods：The study subjects comprised a nationally representative sample of 33,569 adults > 20 years of age who were recruited in the National Health and Nutrition Examination Survey between 1999 and 2014. Anthropometric data, including weight, height, and WC, were measured at each of the eight waves using consistent methodology. Death and underlying causes of death were ascertained through 31 December 2015. The association between central obesity and mortality were determined using weighted Cox proportional hazards regression models. Results：A total of 4013 deaths occurred during a median follow-up of 7.33 years (263,029 person-years). Compared with the subjects in WtHR tertile 1, the subjects in tertiles 2 and 3 were at a higher risk of mortality from all-cause (tertile 2-hazard ratio [HR]: 1.29; 95% confidence interval [CI]: 1.13–1.47; tertile 3-HR: 1.96; 95% CI: 1.64–2.34) and cardiovascular diseases [CVD] (tertile 2-HR: 1.40; 95% CI: 1.09–1.79; tertile 3-HR: 2.00; 95% CI: 1.47–2.73). Similarly, compared with the subjects in WC tertile 1, the subjects in tertiles 2 and 3 were at a higher risk of mortality from all-cause (tertile 2- HR: 1.15; 95% CI: 1.00–1.31; tertile 3-HR: 1.39; 95% CI: 1.15–1.67) and CVD (tertile 2-HR: 1.48; 95% CI: 1.14–1.93; tertile 3-HR: 1.74; 95% CI: 1.26–2.42). Restricted cubic spline analyses revealed an S-shaped and linear dose-relationship between WtHR and WC with all-cause mortality. Moreover, a WtHR > 0.58 or a WC > 0.98m was shown to be a risk factor for all-cause mortality. Conclusions：Central obesity was significantly associated with increased risk of all-cause and CVD-related mortality, especially heart diseases-related mortality, even among normal weight adults. In addition to weight control, guideline designer should provide recommendations for people to decrease abdominal fat accumulation, in their effort to reduce mortality risk in later life.